Analisis Mekanisme Pembiayaan Pesona (Pembelian Barang Serbaguna) Menggunakan Akad Murabahah Di KSPPS Nuri Jawa Timur Cabang Pegantenan - Samsul Arifin (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
The Murabaha contract is one of several contracts used in Sharia cooperatives. A Murabaha contract is a contract of buying and selling goods at the original price with an additional agreed profit. In this contract, the member or customer knows the original price and the price given to the member or customer so that they both know and there is no element of gharar in it. This study aims to find out how the application of murabahah contracts on financing products at KSSPPS Nuri East Java and whether the application of Murabaha contracts on financing products is in accordance with sharia. regarding Murabaha contracts on savings products and looking theoretically at what is applied in banks, this study uses a qualitative method, namely a method by analyzing research results that produce descriptive analysis data. In addition, data collection was carried out by direct interviews with KSPPS Nuri Jatim Cab. Pegantenan, Customer Nuri East Java and Academics of Islamic Economics. The results of the research are savings products in Nuri East Java using a murabahah mutlaqah contract, with a profit ratio of 25:75 (25 for customers and 75 for banks).